Negotiating Qur’anic Interpretive Authority in the Age of Artificial Intelligence in Aceh - Azizi, Afkar; Nurullah, Nurullah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
Artificial intelligence (AI) is increasingly used in Qur’anic learning through tools that search, translate, recommend, and generate explanatory outputs. While these technologies expand access to Qur’anic resources, they also raise questions about interpretive authority when religious meanings are mediated by automated systems. This study examines how boundaries for AI use are articulated in Qur’anic learning and interpretation in Aceh. Using a qualitative design, the research draws on semi-structured interviews with ulama affiliated with dayah (traditional Islamic boarding schools in Aceh). The data were analysed thematically to trace how authority was framed, where limits of use were drawn, and what educational risks were anticipated. The findings show that AI is generally regarded as mubaḥ for limited technical purposes, accompanied by iḥtiyat to safeguard aqidah and reduce uncritical reliance on machine-generated outputs. Interpretive credibility is understood to remain anchored in teacher-guided transmission through talaqqi and sanad, alongside the cultivation of adab and dirayah. AI is restricted from activities that resemble tafsir, particularly where contextual reasoning (including asbab al-nuzul), methodological discipline, and sustained engagement with the classical turath are required. Although AI offers practical benefits for teachers in preparation and administration, it is also associated with concerns about student dependency, weakened study discipline, and reduced engagement with demanding texts. The study shows how epistemic norms in ulum al-Qur'an are operationalised as practical boundaries that conditionally accommodate AI in Qur’anic learning while protecting interpretive authority in dayah contexts in Aceh.